MENINGKATKAN KEMAMPUAN MENULIS PUISI MELALUI METODE KARYA WISATA DENGAN TEKNIK INKUIRI (CTL) PADA SISWA KELAS VIII.8 SMP NEGERI 7 MATARAM TAHUN PELAJARAN 2015-2016 - NI MADE LAMI WIJATI (Universitas Mahasaraswati Mataram, 2018)
Literary works is one of the cultural results that use language as a tool of creativity, while Indonesian language and literature should be taught to students through a particular approach in accordance with the nature and function. The approach of literary learning emphasizes more on the appreciation of literature so that the right approach to be used is apresiasiive approach. In learning to write poetry requires certain techniques so that the poetry can meet the requirements of a poem for example by using diction (choice of words) majas (style of language), the arrangement of taxation (rima).All this time the process of learning to write poetry is quite difficult to do by students, because they have different skills in writing poetry. To help students in generating their imagination the author uses Inquiry Technique (CTL) through the method of tourism work. The research conducted in these two cycles shows significant improvement from cycle I to cycle II. The results of the research that has been conducted, can give an idea of the improvement of the ability to write poetry of students of class VIII.8 SMP Negeri 7 Mataram, with Inquiry technique (CTL) study tours. Thus, the teacher as a teacher can use the technique of Inquiry (CTL) through the method of tourism work as one of the learning techniques in writing poetry so that all students can be actively involved, the students easily reveal their imagination